SUPPRESSION OF THE PIGMENT-SYNTHESIZING CAPACITY OF BACTERIA WITH HEAVY METALS IONS - О. Ф. Рильський; П. I. Гвоздяк (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2009)
The results obtained during the investigation of the pigment-synthesizing capacity of bacteria in conditions of stressful factors action are represented. The major attention was payed on the study of heavy metals action on the pigment-synthesizing capacity of bacteria. The concentration limit to the loss of the pigment-synthesizing capacity and bacteria growth for some metals, has been established. Synthesis of a pigment at S. marcescens MP-141 at concentration of Cu (II) of 80 mg/l amplifies at addition of prolin in medium.